AKUNTABILITAS PENGELOLAAN PROGRAM PEMERINTAH TERHADAP PENGAIRAN AIR TANAH DI DESA BINA BARU KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Naidah Naidah (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
The purpose of the study is to find out how the accountability of government program management for groundwater irrigation is in the village of Bina Baru, Kulo district, Sidenreng Rappang district and to find out what factors affect the accountability of government program management for groundwater irrigation in Bina Baru village, Kulo district, Sidenreng Rappang district. The population of this study was 35 people, and the total sample was 35 people. The data collection techniques used in this study were (1) observation, (2) interviews, (3) questionnaires, and (4) literature studies. The collected data was then analyzed using frequency and percentage tables. The results of this study indicate that the Accountability of Government Program Management for Groundwater Irrigation in Bina Baru Village, Kulo District, Sidenreng Rappang Regency with a value of 70% good category. The factors that influence the Accountability of Government Program Management on Groundwater Irrigation in Bina Baru Village, Kulo District, Sidenreng Rappang Regency, namely Communication factors 72%, resources 68%, bureaucratic structure 70%, disposition of implementers 67%, with achievements 69.25% category good.